Uncovering the Antioxidant Power: Investigating the Skin and Flesh of Crystal Guava with Chloroform and Methanol Extractions and DPPH Assay - Aulia Ulmillah; Arif Alghifari; Nurhaida Widiani (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Crystal guava (Psidium guajava var. crystal) is one type of guava plant that has high economic value due to its thick flesh and few seeds. The crystal guava plant is believed to have antioxidant activity, which is a substance that can prevent the formation of free radicals in the body. This research aims to determine the level of antioxidants in chloroform and methanol extracts of the skin and flesh of crystal guava fruit using the DPPH method. Samples were taken through a stepwise maceration process and solvents of chloroform and methanol, then analyzed using probit analysis and SPSS 25 software. The results of the study showed that both chloroform and methanol extracts of the skin and flesh of crystal guava fruit have antioxidant activity. The results showed that the IC50 value of the chloroform extract of crystal guava fruit skin is 218.88 ppm and is classified as moderate, the methanol extract of crystal guava fruit skin is 89.78 ppm and is classified as strong, the chloroform extract of crystal guava fruit flesh is 270.56 ppm and is classified as weak, and the methanol extract of crystal guava fruit flesh is 185.72 ppm and is classified as moderate.